Robotic assisted laparoscopic radical prostatectomy with the new surgical robot HugoTM RAS in a man with proctocolectomy and restorative ileal pouch-anal anastomosis. The first European urological step-by-step procedure - Totaro A; Scarciglia E; Ragonese M; Cretì A; Bizzarri FP; Campetella M; Gandi C; Palermo G; Racioppi M; Sacco E (Archive of Urological Research - Peertechz Publications, 2023)
Robotic-Assisted Laparoscopic Radical Prostatectomy (RARP) is the gold standard surgical treatment for localized clinically significant prostate cancer. In patients undergone previous abdominal or pelvic surgery, it can be difficult to perform and it is also contraindicated execution of radiotherapy. We have described step-by-step the first case of RARP performed with the robotic system HugoTM RAS in a patient previously subjected to proctocolectomy and ileal pouch-anal anastomosis packaging for ulcerative colitis. The procedure was found to be safe and feasible, with intra- and post-operative data overlapping those of the same procedure in the general population. Execution by an experienced surgeon is in any case recommended.